"A Lot of Things Passed Me by": Rural Stroke Survivors' and Caregivers' Experience of Receiving Education From Health Care Providers. Issue 1 (22nd June 2015) - Danzl, Megan M.; Harrison, Anne; Hunter, Elizabeth G.; Kuperstein, Janice; Sylvia, Violet; Maddy, Katherine; Campbell, Sarah
Abstract: Purpose: The purpose of this study is to examine rural Appalachian Kentucky stroke survivors' and caregivers' experiences of receiving education from health care providers with the long‐term goal of optimizing educational interactions and interventions for an underserved population. Methods: An interprofessional research team, representing nursing, occupational therapy, physical therapy, and speech language pathology, conducted a qualitative descriptive study involving semistructured interviews with 13 stroke survivors and 12 caregivers. Qualitative content analysis included predetermined and emerging coding. This article presents an in‐depth analysis of a subset of data from the coding scheme of a larger study that examined the overall experience of stroke for participants. Findings: Findings are presented within a developing model of patient and caregiver education constructs including providers and receivers of education and the content, timing, and delivery of information. Conclusions: Understanding the experience of receiving education for survivors and caregivers will help practitioners provide the right education, to the right people, at the right time, and in the right way to better support underserved groups. Improving patient and caregiver education is paramount to supporting health behavior change to optimize life poststroke and prevent future strokes. Our results suggest the need for improved access to educational providers, proactive identification of informational needs by providers, greater inclusion of caregivers in education, enhanced communication with information provision, and education from multiple providers using multiple delivery methods at multiple time points.